THE PRESSURE AND TEMPERATURE STABILITY LIMITS OF LAWSONITE: IMPLICATIONS FOR H2O RECYCLING IN SUBDUCTION ZONES - Pawley A.R. (My University, 1994)
The stability relations of lawsonite, CaAl2Si2O7(OH)2H2O, have been investigated at pressures of 6 to 14 GPa and temperatures of 740 to ˜1150°C in a multi-anvil apparatus. Experiments used the bulk composition lawsonite+H2O to determine the maximum stability of lawsonite. Lawsonite is stable on its own bulk composition to a pressure of ˜13.5 GPa at 800°C, and between ˜6.5 and 12 GPa at 1000°C. Its composition does not change with pressure or temperature. All lawsonite reactions have grossular, vapour and two other phases in the system Al2O3-SiO2-H2O (ASH) on their high-temperature side. A Schreinemakers analysis of the ASH phases was used to relate the reactions to each other. At the lowest pressures studied lawsonite breaks down to grossular+kyanite+coesite+vapour in a reaction passing through ˜980°C at 6 GPa and ˜1070°C at 9 GPa. Above 9 GPa the reactions coesite=stishovite and kyanite+vapour=topaz-OH are crossed. The maximum thermal stability of lawsonite is at ˜1080°C, at ˜9.4 GPa. At higher pressures the lawsonite breakdown reactions have negative slopes. The reaction lawsonite=grossular+topaz-OH+stishovite+vapour passes through ˜1070°C at 10 GPa and ˜1010°C at 12 GPa. At 14 GPa, ˜740–840°C, lawsonite is unstable relative to the assemblage grossular+diaspore+vapour+a hydrous phase with an Al:Si ratio of 1:1. Oxide totals in electron microprobe analyses suggest that the composition of this phase is AlSiO3(OH). Two experiments on the bulk composition lawsonite+pyrope [Mg3Al2Si3O12] show that at 10 GPa the reaction lawsonite=Gr-Pyss+topaz-OH+stishovite+vapour is displaced down temperature from the end-member reaction by ˜200°C for a garnet composition of Gr20Py80. Calculations suggest similar temperature displacements for reaction between lawsonite and Gr-Py-Alm garnets of compositions likely to occur in high-pressure eclogites. Temperatures in subduction zones remain relatively low to considerable depth, and therefore slab P-T paths can be within the stability field of lawsonite from the conditions of its crystallisation in blueschists and eclogites, up to pressures of at least 10 GPa. Lawsonite contains 11.5 wt% H2O, which when released may trigger partial melting of the slab or mantle, or be incorporated in hydrous phases such as the aluminosilicates synthesised here. These phases may then transport H2O to an even greater depth in the mantle.